Polymer composite using natural calcium source, elm extract and carboxylate salts and preparation method thereof
A polymer composite with a natural calcium source and carboxylate salt enhances dispersibility and adhesion, addressing impact strength and heat resistance issues, suitable for high-strength, lightweight applications.
Patent Information
- Application Number
- KR1020240004735
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-01-11
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2044-01-11
AI Technical Summary
Existing polymer-nanoclay composites face limitations in impact strength and heat resistance, hindering their widespread application despite improved mechanical properties and lightweighting.
A polymer composite is developed using a natural calcium source with a particle size of 0.5 μm or less, enhanced by hydrogen bonding with a carboxylate salt to improve dispersibility and adhesion, incorporating elm tree extract to strengthen interfacial bonding.
The composite exhibits improved impact resistance and heat distortion temperature, enabling its use in structural materials requiring high strength and low specific gravity, such as automotive parts and electronic components.
Smart Images

Figure 112024004057398-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a polymer composite comprising a natural calcium source, elm tree extract, and a carboxylate salt, and a method for manufacturing the same. More specifically, the invention relates to a polymer composite having excellent heat distortion temperature characteristics and impact resistance, in which intermolecular forces are increased through hydrogen bonding between the polymer and fillers within the polymer resin, and a method for manufacturing the same. Background Technology
[0003] Polymer composites reinforced with inorganic fillers are replacing competing materials such as metals, ceramics, and wood in various industrial fields due to their excellent mechanical properties, superior moldability, and lightweighting effects. In particular, the applications of polymer composites possessing the lightweighting, dimensional stability, and heat resistance required in the automotive, electrical, and electronic materials sectors are expanding.
[0004] Recently, polymer-nanoclay composites have emerged as a method to enhance lightweighting and recyclability while maintaining the improved properties of such polymer composites, and various approaches are being proposed. While these polymer-nanoclay composites offer superior overall mechanical properties, such as stiffness, and lightweighting compared to conventional polymer composites containing common inorganic additives like talc, their application expansion is significantly limited due to the drawback of impact strength falling to the level of existing composites. As such, although attempts to manufacture performance-enhanced polymer composites through various methods continue, there is a need for the development of technologies that can simultaneously satisfy economic feasibility and performance requirements such as impact resistance and heat resistance. Prior art literature
[0006] (Patent Document 0001) KR 10-1780102 A (Patent Document 0002) US 4764326 B (Patent Document 0003) US 4810734 B The problem to be solved
[0007] The inventors have completed the present invention by discovering that the dispersion ability of a polymer composite is significantly enhanced by maintaining the particle size after grinding the natural calcium source to 0.5 μm or less and preventing the aggregation reaction as much as possible with a carboxylate salt.
[0008] The present invention aims to overcome the limitations of the aforementioned prior art. One objective of the present invention is to provide a polymer composite with improved impact resistance and heat distortion temperature by utilizing a natural calcium source to enhance impact resistance through the property of strong adhesion between polymers via hydrogen bonding, and further enhancing dispersibility by using a carboxylate salt having ionic bonding.
[0009] The objectives of the present invention are not limited to those mentioned above, and other unmentioned objectives will be clearly understood by those skilled in the art from the description below. means of solving the problem
[0011] One aspect of the present invention for solving the above-mentioned problem is,
[0012] This invention relates to a polymer composite comprising a polymer resin, a natural calcium source, elm extract, and a carboxylate salt.
[0013] Polymer resins usable in the present invention may include one or more selected from the group consisting of petrochemical polypropylene, natural polypropylene, polypropylene copolymer, ethylene-propylene copolymer, polypropylene-ethylene octene copolymer, and polypropylene blending polymer.
[0014] The above natural calcium source may be one or more selected from the group consisting of bovine bone, fish bone, eggshell, seashell, abalone shell, oyster shell, and seaweed.
[0015] The above carboxylate salts are potassium bitartrate, sodium 1-butanesulfonate, sodium propionate, sodium hexanoate, sodium octanoate, sodium decanonate, sodium dodecanoate, sodium benzoate, sodium butyrate, sodium acetate, potassium benzoate, lithium acetate, lithium benzoate, potassium acetate, potassium benzoate, and ammonium acetate. It may be one or more selected from the group consisting of Acetate, Ammonium Benzoate, and Potassium Sodium Tartrate Tetrahydrate.
[0016] The polymer composite of the present invention may contain 1 to 20 parts by weight of elm extract, 1 to 10 parts by weight of carboxylate salt, and 1 to 60 parts by weight of natural calcium source per 100 parts by weight of polymer resin.
[0017] Another aspect of the present invention for solving the above-mentioned problem is,
[0018] Step of removing foreign substances from the natural calcium source and crushing it;
[0019] A calcination step of calcining the crushed natural calcium source at 1,000~1,300℃;
[0020] A step of spraying elm extract and carboxylate salt onto a calcined natural calcium source and then drying; and
[0021] The present invention relates to a method for manufacturing a polymer composite, characterized by including the step of mixing a crushed natural calcium source obtained in the previous step, an elm extract, and a carboxylate salt into a polymer resin to form a mixture.
[0022] The above method may further include a step of forming the mixture.
[0023] The polymer usable in the present invention may be selected from the group of biodegradable polymers consisting of PLA (poly lactic acid), PBS (poly butylene succinate), PBSA (poly butylene succinate adipate), PBAT (poly butylene adipate-co-terephthalate), PCL (poly(caprolactone)), PHA (poly(hydroxyalkanoates)), and PGA (poly(glycolic acid)).
[0024] The natural calcium source usable in the present invention may be one having a particle size of 0.03 μm or more and 0.5 μm or less after heat calcination.
[0025] The above elm extract can be prepared by drying the stem, stem bark, root, and / or root bark of an elm tree using a hot air dryer at 70°C for 5 hours for the leaves and at 60°C for 8 hours for the stem (stem bark) and root (root bark), then grinding the elm tree in a grinder to a size of 100 mesh to produce a ground elm tree material, adding 30g of the ground material to 200ml of water and 100ml of ethanol and performing reflux extraction at 70°C for 8 hours, then concentrating under reduced pressure in a rotary evaporator and removing impurities using a paper filter.
[0026] The above carboxylate salts are potassium bitartrate, sodium 1-butanesulfonate, sodium propionate, sodium hexanoate, sodium octanoate, sodium decanonate, sodium dodecanoate, sodium benzoate, sodium butyrate, sodium acetate, potassium benzoate, lithium acetate, lithium benzoate, potassium acetate, potassium benzoate, and ammonium acetate. One or more selected from the group consisting of Acetate, Ammonium Benzoate, and Potassium Sodium Tartrate Tetrahydrate may be used. Effects of the invention
[0028] The polymer composite using the natural calcium source, carboxylate salt, and elm tree extract of the present invention described above can provide a polymer composite with improved impact resistance and heat distortion temperature by increasing the interfacial force between polymer matrices and increasing the dispersibility of the natural calcium source particles.
[0029] By utilizing the polymer composite of the present invention, it can be widely used as an exterior material and structural stabilization material in fields such as construction and civil engineering, structures, or electrical and electronic components that require properties of low specific gravity and high impact strength, as well as as a diverse interior material for automobiles with lightweight and high strength for automotive parts. Brief explanation of the drawing
[0031] Figure 1 is a photograph of an elm tree extract included in a polymer composite of one embodiment of the present invention. Figure 2 shows a photograph of crushed eggshells, a natural calcium source, and EDS data added to a polymer composite according to one embodiment of the present invention. Figure 3 is a graph showing the Izod impact strength of a polymer composite according to the type of natural calcium source in a polymer composite according to one embodiment of the present invention. Figure 4 is a graph showing the heat distortion temperature (HDT) of a polymer composite according to the type of natural calcium source in a polymer composite according to one embodiment of the present invention. Figure 5 is a graph showing the flexural modulus of a polymer composite according to the content of shellfish, a natural calcium source, in a polymer composite according to one embodiment of the present invention. Specific details for implementing the invention
[0032] Specific embodiments of the present invention will be described in more detail below with reference to the attached drawings.
[0033] One aspect of the present invention relates to a polymer composite comprising a polymer resin, elm extract, a natural calcium source, and a carboxylate salt.
[0034] In this invention, elm tree extract is used to enhance the interfacial bonding strength between the polymer matrix and the inorganic filler, natural calcium source, thereby increasing the adhesion between the natural calcium source and the polymer. The elm tree extract is a viscous solution that enables the adhesion between the calcium carbonate and the polymer. Additionally, to improve the dispersibility of nano-sized natural calcium source, a carboxylate salt is used to act as a dispersant that facilitates the mixing of hydrophobic and hydrophilic substances.
[0035] In the present invention, one or more polyolefin resins selected from the group consisting of petrochemical polypropylene, natural polypropylene, polypropylene copolymer, ethylene-propylene copolymer, polypropylene-ethylene octene copolymer, and polypropylene blend may be used as the polymer resin constituting the polymer composite, but are not necessarily limited to these.
[0036] In addition, in a preferred embodiment, one or more biodegradable polymers selected from the group consisting of PLA (poly lactic acid), PBS (poly butylene succinate), PBSA (poly butylene succinate adipate), PBAT (poly butylene adipate-co-terephthalate), PCL (poly(caprolactone)), PHA (poly(hydroxyalkanoates)), and PGA (poly(glycolic acid)) may be selected and used as the polymer resin.
[0037] In the present invention, natural calcium sources may be selected from bovine bone, fish bone, eggshell, clam shell, abalone shell, oyster shell, seaweed, etc. In particular, eggshell components contain 90.9% calcium carbonate (CaCO3), 7.56% protein, 0.24% lipids, and large amounts of other inorganic components such as phosphorus and magnesium.
[0038] Seaweeds include brown algae such as kelp, wakame, and hijiki, green algae such as sea lettuce, and red algae such as laver and agar. Red algae contain more than 50% calcium per dry weight compared to other seaweeds, so they can be used more advantageously in the present invention.
[0039] Conventionally, to reduce the amount of expensive resin used in polymer composites, calcium salts with particle sizes typically ranging from 1 to 50 μm were used. However, it is known that such calcium salts do not significantly improve physical properties such as impact resistance and heat resistance of the filled polymer composites, and the main reason for this was the weak interfacial bonding force between calcium carbonate and the polymer. In the present invention, natural calcium sources that can be used may have a particle size of 0.5 μm or less after heat sintering.
[0040] In the present invention, a carboxylate salt is used to improve the dispersibility of nano-sized natural calcium sources, thereby ensuring that hydrophobic and hydrophilic materials are well mixed. To disperse hydrophilic calcium carbonate (CaCO3) into a hydrophobic polymer, the calcium carbonate (CaCO3) is surface-treated with a carboxylate salt. To prevent the inhibition of dispersion performance caused by aggregation and the formation of large aggregates when the natural calcium salt is ground to a particle size of 0.5 μm or less, the surface of the ground particles is treated with a carboxylate salt to activate repulsive force, thereby preventing precipitation and improving dispersion performance.
[0041] In the present invention, the average particle size of the natural calcium salt is within the range of 0.03 μm or more and 0.5 μm or less. If the average particle size of the natural calcium salt is less than 0.03 μm, polarization occurs during production, resulting in uneven input and aggregation of particles, which reduces resin dispersibility and lowers quality; if the average particle size exceeds 0.5 μm, it hinders the improvement of rigidity and heat resistance by inorganic fillers and may cause differences in physical properties.
[0042] In the present invention, to increase the interfacial bonding strength between a polymer and a natural calcium source, an elm extract capable of increasing the adhesion between a natural calcium source and a polymer is used. The elm extract is a sticky solution that improves the adhesion between calcium carbonate and a polymer. The elm (Ulmus davidiana var. japonica) is a deciduous broad-leaved tree belonging to the Ulmaceae family. It is known that the bark of this elm contains components such as flavonoids, saponins, tannins, mucilage (herbal component: *Ilwolseogak*), β-sitosterol, phytosterol, sigmasterol, tannins, and fattyoil.
[0043] The above carboxylate salts are potassium bitartrate, sodium 1-butanesulfonate, sodium propionate, sodium hexanoate, sodium octanoate, sodium decanonate, sodium dodecanoate, sodium benzoate, sodium butyrate, sodium acetate, potassium benzoate, lithium acetate, lithium benzoate, potassium acetate, potassium benzoate, and ammonium acetate. One or more selected from the group consisting of Acetate, Ammonium Benzoate, and Potassium Sodium Tartrate Tetrahydrate may be used, but are not necessarily limited to these.
[0044] In the present invention, a natural calcium source may be included in an amount of 1 to 60 parts by weight per 100 parts by weight of polymer resin. If the content is less than 1 part by weight, the effect of increasing the stiffness of the resin composition is insufficient, and if it exceeds 60 parts by weight, the impact strength of the polymer composite may be lowered.
[0045] In a preferred embodiment, elm extract is included in an amount of 1 to 20 parts by weight per 100 parts by weight of polymer resin. If the content is less than 1 part by weight, the effect of increasing intermolecular forces between the polymer and the natural calcium salt becomes insufficient, and if it exceeds 20 parts by weight, processability may be reduced.
[0046] In a preferred embodiment, the carboxylate salt is included in an amount of 1 to 10 parts by weight per 100 parts by weight of the polymer resin. If the content is less than 1 part by weight, the effect of mixing the hydrophobic material and the hydrophilic material well is insufficient, and if it exceeds 10 parts by weight, the impact strength of the polymer composite may be lowered.
[0047] Another aspect of the present invention relates to a method for manufacturing a polymer composite. When manufacturing a polymer composite by the method of the present invention, a natural calcium source is first washed to remove foreign substances and crushed. In the method of the present invention, the natural calcium source is prepared into high-density pellets by using elm extract as an interfacial adhesive and a carboxylate salt as a dispersant, and by imparting functionality, the powdered natural calcium is made to be homogeneously mixed within the polymer. To this end, it is preferable to feed the natural calcium source into a bead mill with a particle size of 0.3 mm and grind it to an ultrafine size of 0.5 μm or less, more preferably 0.3 μm or less.
[0048] In the present invention, petrochemical polypropylene, natural polypropylene, polypropylene copolymer, ethylene-propylene copolymer, polypropylene-ethylene octene copolymer, and polypropylene blend may be used as polyolefin resins constituting the polymer composite, but are not necessarily limited to these.
[0049] In addition, a biodegradable polymer can be used in the step of manufacturing the polymer in the form of a composite, and the biodegradable polymers that can be used are one or more biodegradable polymers selected from the group consisting of PLA (poly lactic acid), PBS (poly butylene succinate), PBSA (poly butylene succinate adipate), PBAT (poly butylene adipate-co-terephthalate), PCL (poly(caprolactone)), PHA (poly(hydroxyalkanoates)), and PGA (poly(glycolic acid)).
[0050] Next, the crushed natural calcium source is calcined at 1,000 to 1,300°C. The natural calcium source used in the present invention is dried, crushed, and then calcined, and then re-dried and crushed again. The calcination step by heating is intended to ensure that only inorganic substances, including calcium, remain by completely burning and removing various bacteria, organic substances, and various impurities.
[0051] Examples of natural calcium sources usable in the present invention include cow bones, fish bones, eggshells, seashells, abalone shells, oyster shells, and seaweed, but are not necessarily limited to these, and any natural calcium raw material containing calcium can be used as a calcium source.
[0052] The carboxylate salts usable in the present invention include potassium bitartrate, sodium 1-butanesulfonate, sodium propionate, sodium hexanoate, sodium octanoate, sodium decanonate, sodium dodecanoate, sodium benzoate, sodium butyrate, sodium acetate, potassium benzoate, lithium acetate, lithium benzoate, potassium acetate, and potassium benzoate. One or more selected from the group consisting of ammonium acetate, ammonium benzoate, and potassium sodium tartrate tetrahydrate may be used.
[0053] A mixture is prepared by mixing the above-mentioned dried natural calcium source crushed material with elm extract and carboxylate salt as additives.
[0054] In a preferred embodiment, natural elm extract is included in an amount of 1 to 20 parts by weight per 100 parts by weight of polymer resin. In a preferred embodiment, carboxylate salt is included in an amount of 1 to 10 parts by weight per 100 parts by weight of polymer resin. In a preferred embodiment, natural calcium source may be included in an amount of 1 to 60 parts by weight per 100 parts by weight of polymer resin.
[0055] The polymer composite of the present invention can provide the advantage of improved impact resistance and heat distortion temperature by increasing interfacial forces between polymer matrices and increasing the dispersibility of natural calcium source particles. Therefore, since the polymer composite of the present invention is lightweight yet possesses increased mechanical strength, it can be used as a structural material expected to be applied in automobiles, electronic information, construction and civil engineering, etc.
[0056] The present invention will be specifically explained by the following examples, but the present invention is not limited by these examples.
[0057] Examples
[0058] Preparation Example 1: Preparation of elm extract
[0059] The stem, stem bark, roots, and root bark of the elm tree were washed in an ultrasonic cleaner for 20 minutes, completely dried, and then dried using a hot air dryer at 70°C for 5 hours for the leaves and at 60°C for 8 hours for the stem (stem bark) and roots (root bark). Afterward, the elm tree was ground in a grinder to a size of 100 mesh to prepare the elm tree powder. 30g of the ground powder was placed in 200ml of water and 100ml of ethanol and reflux extracted at 70°C for 8 hours. Then, the mixture was concentrated under reduced pressure in a rotary evaporator and impurities were removed using a paper filter to prepare the elm tree extract.
[0061] Preparation Example 2: Eggshell calcium carbonate (CaCO₃) 3 ) Particle manufacturing
[0062] 1 kg of eggshells were washed in an ultrasonic cleaner for 20 minutes, then completely dried using a hot air dryer at 60°C for 8 hours. The eggshell calcium particles were ground in a grinder to a size of 400 mesh (37 µm) to produce crushed eggshell calcium particles. The primary crushed material was fed into a bead mill with a particle size of 0.3 mm to reduce the particle size to 0.3 µm or less. The particles thus ground were calcined in an electric high-temperature kiln at 1,300°C for 10 minutes to obtain 850 g of calcined material.
[0064] Preparation Example 3: Seashell calcium carbonate (CaCO₃) 3 ) Particle manufacturing
[0065] 1 kg of seashells were washed in an ultrasonic cleaner for 20 minutes, completely dried, and dried using a hot air dryer at 60°C for 8 hours. The 1 kg of seashells were ground in a grinder to a size of 400 mesh and calcined in an electric high-temperature kiln at 1,300°C for 10 minutes to obtain 850 g of calcined product. The seashell calcium particles were ground in a grinder to a size of 30 mesh to produce crushed seashell calcium particles. The primary crushed material was fed into a bead mill with a particle size of 0.3 mm to reduce the particle size to 0.3 µm or less. The particles ground in this manner were calcined in an electric high-temperature kiln at 1,300°C for 10 minutes to obtain 800 g of calcined product.
[0067] Preparation Example 4: Seaweed calcium carbonate (CaCO₃) 3 ) Particle manufacturing
[0068] 1 kg of dried red algae is finely powdered to a mesh size of 100 or less using a grinder. The finely powdered red algae is calcined at 1000–1200°C for 1 hour to obtain approximately 520 g of pure inorganic material with the organic matter completely removed, at which point the calcium content is approximately 219 g. The calcined red algae is dried at room temperature for 2 days. Drying the calcined red algae at room temperature is done to prevent the denaturation of calcium. The cooled red algae is finely powdered again to a mesh size of approximately 70 using a grinder. The primary powder is fed into a bead mill with a particle size of 0.3 mm to make it 0.3 µm or less.
[0070] Comparative Example 1: Polypropylene / General Purpose Calcium Carbonate (CaCO₃) 3 )Manufacture of polymer composite pellets
[0071] Polypropylene (manufactured by Honam Petrochemical Co., Ltd.) was used as the polymer resin. 70 parts by weight of polypropylene resin and 30 parts by weight of calcium carbonate were mixed in a high-temperature rotary mixer, and then extruded using a twin-screw extruder (BA-30, BaU Tek) to produce a pellet-shaped masterbatch. The extrusion conditions were a barrel temperature of 210°C–220°C and 200 rpm. The prepared pellet samples were injection molded on an ASTM tension bar of a 5 oz Battenfeld molding machine at a barrel temperature of 177°C, a mold temperature of 60°C, and an injection rate of 12.7 mm / sec to produce polypropylene / general-purpose calcium carbonate (CaCO3) polymer composite pellet specimens.
[0073] Example 1: Polypropylene / Eggshell Calcium Carbonate (CaCO₃) 3 ) Preparation of polymer composite pellets
[0074] Polypropylene (manufactured by Honam Petrochemical Co., Ltd.) was used as the polymer resin, and the elm extract obtained in Preparation Example 1 and the eggshell calcium carbonate particles obtained in Preparation Example 2 were mixed in a high-temperature rotary mixer with 60 parts by weight of polypropylene resin, 30 parts by weight of eggshell calcium carbonate (CaCO3), 10 parts by weight of elm extract, and 1 part by weight of sodium benzoate, and then dried. Subsequently, a master batch in the form of pellets was produced by extrusion using a twin-screw extruder (BA-30 BaU Tek). At this time, the extrusion conditions were a barrel temperature of 210°C to 220°C and 200 rpm. The prepared pellet samples were injection molded on an ASTM tension bar of a 5 oz Battenfeld molding machine at a barrel temperature of 177°C, a mold temperature of 60°C, and an injection rate of 12.7 mm / sec to produce polypropylene / eggshell calcium carbonate (CaCO3) polymer composite pellet specimens.
[0076] Example 2: Polypropylene / Shell Calcium Carbonate (CaCO₃) 3 ) Preparation of polymer composite pellets
[0077] Polypropylene (manufactured by Honam Petrochemical Co., Ltd.) was used as the polymer resin. The extract of *Euonymus japonicus* obtained in Preparation Example 1 and the seashell calcium particles prepared in Preparation Example 3 were mixed in a high-temperature rotary mixer with 60 parts by weight of polypropylene resin, 30 parts by weight of seashell calcium (CaCO3) particles, 10 parts by weight of *Euonymus japonicus* extract, and 1 part by weight of sodium benzoate, followed by drying. Subsequently, a masterbatch in the form of pellets was produced by extrusion using a twin-screw extruder (BA-30, BaU Tek). The extrusion conditions were a barrel temperature of 210°C–220°C and 200 rpm. The prepared pellet samples were injection molded on an ASTM tension bar of a 5 oz Battenfeld molding machine at a barrel temperature of 177°C, a mold temperature of 60°C, and an injection rate of 12.7 mm / sec to produce polypropylene / seashell calcium carbonate (CaCO3) polymer composite pellet specimens.
[0079] Example 3: Polypropylene / Seaweed Calcium Carbonate (CaCO₃) 3 ) Preparation of polymer composite pellets
[0080] Polypropylene (manufactured by Honam Petrochemical Co., Ltd.) was used as the polymer resin. The extract of *Euonymus japonicus* obtained in Preparation Example 1 and the seaweed calcium particles prepared in Preparation Example 4 were mixed in a high-temperature rotary mixer with 60 parts by weight of polypropylene resin, 30 parts by weight of seaweed calcium (CaCO3) particles, 10 parts by weight of *Euonymus japonicus* extract, and 1 part by weight of sodium benzoate, followed by drying. Subsequently, a masterbatch in the form of pellets was produced by extrusion using a twin-screw extruder (BA-30, BaU Tek). The extrusion conditions were a barrel temperature of 210°C–220°C and 200 rpm. The prepared pellet samples were injection molded on an ASTM tension bar of a 5 oz Battenfeld molding machine at a barrel temperature of 177°C, a mold temperature of 60°C, and an injection rate of 12.7 mm / sec to produce polypropylene / seaweed calcium carbonate (CaCO3) polymer composite pellet specimens.
[0082] Test Example 1
[0083] The impact strength, heat distortion temperature, and flexural modulus of the injection-molded specimens were measured by the following method and are shown as graphs in Figures 3, 4, and 5.
[0084] (1) Impact strength
[0085] A specimen with dimensions of 63.5 mm x 12.7 mm x 3.2 mm with a notch conforming to ASTM D256 was prepared. The Izod impact strength of the specimen was measured according to the standard test method of ASTM D256 using a Digital impact tester (QM (700A), manufactured by QMESYS).
[0086] (2) Heat distortion temperature
[0087] The heat distortion temperature (HDT) is defined as the maximum temperature at which a material can withstand deformation exceeding a predetermined strain value while under a specific applied load. To verify the improvement in heat resistance of the polymer composite prepared in the examples, a Tinus olsen 303 HDTM heat distortion temperature measuring instrument was used.
[0088] (3) Flex test
[0089] A specimen with dimensions of 80 mm x 10 mm x 4 mm was prepared according to the standard test method of ISO 178. The specimen was placed in a constant temperature and humidity chamber adjusted to a temperature of 23°C and a relative humidity of 50% for 24 hours, after which it was subjected to a bending test. The flexural modulus (GPa) of the specimen was measured according to the standard test method of ISO 178 using an Instron Universal Testing Machine (UTM).
[0090] As shown in FIGS. 3 to 5, it can be confirmed that the polymer composite of the present invention has increased performance in impact strength, heat distortion temperature, and flexural modulus compared to a general-purpose calcium carbonate-containing composite in polypropylene resin under conditions containing natural calcium salt, elm extract, and carboxylate salt.
[0091] Referring to Fig. 4, the results of measuring the heat resistance of the polymer composite using an HDT (heat distortion temperature) tester showed that when natural calcium salts were added as in the present invention, the HDT was improved by more than 13°C regardless of the type.
[0092] Although the present invention has been described above with reference to preferred embodiments, it is not limited to the above-mentioned embodiments, and various changes or modifications may be made by those skilled in the art within the scope of the invention without departing from the spirit of the invention. Accordingly, the true scope of protection of the present invention should be determined by the appended claims.
Claims
Claim 1 A polymer composite comprising 100 parts by weight of polymer resin, 1 to 60 parts by weight of natural calcium source, 1 to 20 parts by weight of elm extract; and 1 to 10 parts by weight of carboxylate salt, wherein the natural calcium source has a particle size of 0.03 μm or more and 0.5 μm or less. Claim 2 A polymer composite according to claim 1, characterized in that the polymer resin is one or more polyolefin resins selected from the group consisting of petrochemical polypropylene, natural polypropylene, polypropylene copolymer, ethylene-propylene copolymer, polypropylene-ethylene octene copolymer, and polypropylene blending polymer. Claim 3 A polymer composite according to claim 1, characterized in that the natural calcium source is one or more selected from the group consisting of bovine bone, fish bone, eggshell, seashell, abalone shell, oyster shell, and seaweed. Claim 4 In claim 1, the carboxylate salt is potassium bitartrate, sodium 1-butanesulfonate, sodium propionate, sodium hexanoate, sodium octanoate, sodium decanonate, sodium dodecanoate, sodium benzoate, sodium butyrate, sodium acetate, potassium benzoate, lithium acetate, lithium benzoate, potassium acetate, potassium benzoate, A polymer composite characterized by being one or more selected from the group consisting of ammonium acetate, ammonium benzoate, and potassium sodium tartrate tetrahydrate. Claim 5 delete Claim 6 A method for manufacturing a polymer composite comprising the steps of: removing foreign substances from a natural calcium source and crushing it; calcining the crushed natural calcium source at 1,000 to 1,300°C; spraying elm tree extract and a carboxylate salt onto the calcined natural calcium source and then drying it; and mixing the crushed natural calcium source obtained in the previous step, the elm tree extract, and the carboxylate salt into a polymer resin to form a mixture, wherein the natural calcium source has a particle size of 0.03 μm or more and 0.5 μm or less, and the elm tree extract is mixed in an amount of 1 to 20 parts by weight, the carboxylate salt in an amount of 1 to 10 parts by weight, and the natural calcium source in an amount of 1 to 60 parts by weight per 100 parts by weight of the polymer resin. Claim 7 A method for manufacturing a polymer composite according to claim 6, wherein the method further comprises the step of molding the mixture. Claim 8 A method for preparing a polymer composite according to claim 6, characterized in that the polymer is selected from the group of biodegradable polymers consisting of PLA (poly lactic acid), PBS (poly butylene succinate), PBSA (poly butylene succinate adipate), PBAT (poly butylene adipate-co-terephthalate), PCL (poly(caprolactone)), PHA (poly(hydroxyalkanoates)), and PGA (poly(glycolic acid)). Claim 9 A method for preparing a polymer composite according to claim 6, wherein the elm tree extract is prepared by using a hot air dryer to dry the stem, stem bark, root, and root bark of an elm tree at 70°C for 5 hours for the leaves and at 60°C for 8 hours for the stem (stem bark) and root (root bark), then grinding the elm tree in a grinder to a size of 100 mesh to produce a ground elm tree material, adding 30g of the ground material to 200ml of water and 100ml of ethanol and performing reflux extraction at 70°C for 8 hours, then concentrating under reduced pressure in a rotary evaporator and removing impurities using a paper filter. Claim 10 In claim 6, the carboxylate salt is potassium bitartrate, sodium 1-butanesulfonate, sodium propionate, sodium hexanoate, sodium octanoate, sodium decanonate, sodium dodecanoate, sodium benzoate, sodium butyrate, sodium acetate, potassium benzoate, lithium acetate, lithium benzoate, potassium acetate, potassium benzoate, A method for manufacturing a polymer composite characterized by comprising one or more selected from the group consisting of ammonium acetate, ammonium benzoate, and potassium sodium tartrate tetrahydrate. Claim 11 delete
Citation Information
Patent Citations
Egg-shell powder filled poly-lactic acid composite material and preparation method thereof
CN101665619A
Method for filling and modifying polypropylene by egg shell powder
CN102002187A
Eggshell powder-blended biodegradable molding
JP2021025021A
Eco-friendly cosmetic container and manufacturing method thereof
KR102222764B1
Polylactic acid-based resin composition, and molded product thereof and method for producing the molded product
JP2008101096A
